Massive Open Online Courses (MOOCs): data on higher education - Al-Rahmi, Waleed Mugahed; Aldraiweesh, Ahmed; Yahaya, Noraffandy; Kamin, Yusri; Zeki, Akram M. (Elsevier, 2019)
The data presented in this article are based on provides a systematic and organized review of 219 studies regarding using of Massive Open Online Courses (MOOCs) in higher education from 2012 to 2017. Consequently, the extant, peer-reviewed literature relating to MOOCs was methodically assessed, as a means of formulating a classification for MOOC-focused scholarly literature. The publication journal, country of origin, researchers, release data, theoretical approach, models, methodology and study participants were all factors used to assess and categorise the MOOC. These data contribute to materials required by readers who are interested in different aspects related to the literature of using Massive Open Online Courses (MOOCs) in higher education. Intention to use, interaction, engagement, motivations and satisfaction were five dynamics assessed in relation to the improvement of MOOCs. Students’ academic performance can be influenced by MOOC which has the advantage of facilitating the learning process through offering materials and enabling the share of information